Modern pharmacotherapy of obesity: molecular mechanisms, clinical efficacy and future therapeutic directions - Selvan, Navneeth (International Journal of Basic & Clinical Pharmacology, 2026)
Obesity is now recognized as a chronic, relapsing, neuroendocrine disease characterised by dysregulation of appetite, impaired energy homeostasis and complex metabolic disturbances. Traditional lifestyle interventions, although foundational, often fail to achieve durable weight reduction because of adaptive biological mechanisms that favour weight regain. Over the past two decades, pharmacotherapy has evolved from modestly effective agents such as orlistat and sympathomimetics to highly potent incretin-based and multi-hormonal peptide therapies capable of inducing double-digit percentage weight loss. This narrative review summarizes contemporary anti-obesity pharmacotherapy with emphasis on molecular mechanisms, pivotal clinical trial data and future therapeutic directions. Literature was identified using PubMed, Scopus and Embase with search terms including “obesity pharmacotherapy”, “orlistat”, “phentermine”, “liraglutide”, “semaglutide”, “tirzepatide”, “cagrilintide” and “retatrutide”. Classical agents such as orlistat, phentermine–topiramate and naltrexone–bupropion typically achieve 3–10% weight loss but are limited by tolerability and safety concerns. GLP-1 receptor agonists (liraglutide and semaglutide) provide substantially greater weight reduction with clinically meaningful improvements in cardiometabolic risk factors. Dual GIP/GLP-1 receptor agonists such as tirzepatide have demonstrated unprecedented efficacy, with up to 22.5% mean weight loss in the SURMOUNT trials. Emerging agents including cagrilintide (amylin analogue) and triple agonists such as retatrutide (GIP/GLP-1/glucagon) are poised to redefine pharmacological obesity treatment. Modern pharmacotherapy for obesity therefore spans a spectrum from older agents with modest efficacy to next-generation multi-agonist peptides approaching bariatric surgery–level outcomes. Rational, individualised drug selection based on comorbidities, tolerability and accessibility will be central to optimising long-term outcomes.